COULD HYBRID IDENTITY FORMATION BE POSSIBLY AVOIDED IN KNOWLEDGE SOCIETY? - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2009)
The article deals with a problem of multicultural education, emphasizing the problem of national identity in the knowledge society. The influence of globalization on national policy for multicultural education is analysed. The new idea of hybridical identity in the context of knowledge society is discussed in the perspective of critical pedagogy, trying to find out, how knowledge society transforms the phenomenon of identity. Some suggestions on how to help educationalists, teachers in these new conditions, especially ctitical thinking and recognition of ideology are explicated. Based on the insights of Lithuanian theoreticians the conservative policy in Lithuania and the role of traditional values are described as the main instruments to preserve the status quo so as to foster traditional national identity. Content analysis of Lithuanian national civic syllabus shows, that there is no attention to dialogue, critical thinking, so it is obvious that assimilatory policy of education is followed, but there are some efforts evident that open mindedness towards other cultures is being developed. So Lithuanian education policy is double-faced, it helps to foster open mindedness of students, but at the same time tries to protect their national identity from hybridedness.